2021
DOI: 10.1039/d0qo01012j
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed, N-directed remote C(sp3)–H azidation and thiocyanation

Abstract: A mild and practical protocol is developed for the synthesis of distal azido and thiocyanato alkylamines via N-directed remote C(sp3)–H functionalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Mechanistic studies revealed that the reaction proceeds through the selective cleavage of the C­(sp 3 )–H bond via the 1,5-HAT process initiated from the N-centered radical 242 – 1 (Scheme b) . At the same time, Liu and co-workers also achieved a similar N-radical directed remote C­(sp 3 )–H azidation using copper catalysts . Later, the Wang group achieved the remote azidation of inert C­(sp 3 )–H bonds of most prevalent alkene 244 by C­(sp 3 )-centered radical relay process using Togni reagent II as the CF 3 source and TMSN 3 as the azide source under iron catalysis (Scheme c) .…”
Section: Azidation Of C–h Bondsmentioning
confidence: 98%
See 1 more Smart Citation
“…Mechanistic studies revealed that the reaction proceeds through the selective cleavage of the C­(sp 3 )–H bond via the 1,5-HAT process initiated from the N-centered radical 242 – 1 (Scheme b) . At the same time, Liu and co-workers also achieved a similar N-radical directed remote C­(sp 3 )–H azidation using copper catalysts . Later, the Wang group achieved the remote azidation of inert C­(sp 3 )–H bonds of most prevalent alkene 244 by C­(sp 3 )-centered radical relay process using Togni reagent II as the CF 3 source and TMSN 3 as the azide source under iron catalysis (Scheme c) .…”
Section: Azidation Of C–h Bondsmentioning
confidence: 98%
“…256 At the same time, Liu and co-workers also achieved a similar N-radical directed remote C(sp 3 )−H azidation using copper catalysts. 257 Later, the Wang group achieved the remote azidation of inert C(sp 3 )−H bonds of most prevalent alkene 244 by C(sp 3 )-centered radical relay process using Togni reagent II as the CF 3 source and TMSN 3 as the azide source under iron catalysis (Scheme 62c). 258 The reaction proceeds under mild conditions to deliver the corresponding 1,6-and 1,7-azidotrifluoromethylated compounds 245 in moderate to good yields with excellent regioselectivity (up to 20 > 1).…”
Section: Azidation Of Aliphatic C−h Bondsmentioning
confidence: 99%
“…Later, they also expanded this system to remote azidation and thiocyanation of unactivated C(sp 3 )–H bonds distal to the amine moiety using TMSN 3 and TMSSCN as nucleophiles. 84…”
Section: Copper-catalyzed Radical Relay In C(sp3)–h Functionalizationmentioning
confidence: 99%
“…Elegant demonstrations of N-radical-mediated remote C­(sp 3 )–H functionalization can be found from the earliest example named the Hofmann–Löffler–Freytag (HLF) reaction for the synthesis of pyrrolidines to the most recent achievements allowing for cross-coupling of the generated alkyl radicals with various nucleophiles via Cu catalysis. Generally, the classic HLF process occurs by the formation of an unstable N–X (X = Cl, Br, I) bond, followed by N-radical generation and then intramolecular 1,5-hydrogen atom transfer (1,5-HAT), halogenation, and cyclization to afford pyrrolidines (Figure ). The interruption of this process via Cu- or Ni-catalyzed trapping of the distal alkyl radicals and subsequent cross-coupling could substantially extend the utility of the HLF reaction.…”
mentioning
confidence: 99%